Petits riens sophocléens : Œdipe à Colone II - Liberman, Gauthier (Hyperboreus, 2021)
This two-part paper, one of a forthcoming series of “Sophoclea” or “*Sophocleuncula”, deals with not a few diﬃcult passages of this poet’s last tragedy Oedipus at Colonos and is meant by its author to contribute to reconsidering the numerous exegetical and critical issues which the text of this unduly neglected drama raises. In this second part an emendation of the famous “Eleusinian” fragment 837 Radt is also suggested.